Peningkatan Pemahaman Siswa Pada Mapel Akidah Akhlak Melalui Tayangan Sinetron Islam KTP - Abd. Rozaq; Tri Adi Setiawan; Arif Rahman Hakim; Ferry Yanto (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
The subject of Aqidah Akhlak plays an important role in shaping students' character and noble morals. However, the material of Aqidah Akhlak is often considered less engaging and difficult for students to understand. Therefore, innovation in teaching methods is needed to address these issues. The Islamic soap opera Islam KTP episode 01, with a storyline close to the daily lives of teenagers, is seen as an effective alternative media for learning. This research is relevant because the soap opera presents the values of Aqidah and Akhlak creatively and entertainingly. This study uses a qualitative approach with a case study design. The research subjects are MA Darussalam Ngoro Jombang students who have watched the Islam KTP soap opera episode 01. Data was collected through observation, in-depth interviews with students and teachers, and documentation. The study results show that the Islam KTP soap opera episode 01 can potentially improve students' understanding of Aqidah Akhlak material. This is evident from students' enthusiasm in participating in discussions after watching the soap opera, as well as the increase in students' understanding of the Aqidah Akhlak concepts presented in the soap opera